STRATEGI PENINGKATKAN KETERAMPILAN PUSTAKAWAN DALAM MENGHADAPI DISRUPSI DIGITAL - Mar’atus Nur Sholehah (Jurnal Manajemen Pendidikan, 2026)
The transformation of libraries into community knowledge hubs is hindered by gaps in human resource competencies, high levels of technology anxiety, resistance to change, and the limitations of conventional training programs, which are rigid and fragmented. This study aims to formulate a holistic, integrative, and dynamic strategic model for enhancing library staff skills in the era of digital disruption. Using a qualitative literature review method with descriptive content analysis, this study examines reputable scientific literature from 2021 to 2026. The results reveal that the success of hybrid service integration is determined by the synthesis of the Three Pillars of Competency: advanced IT skills (data security and big data analysis), active digital literacy and communication (librarians as information counselors), and mental resilience based on positive self-disruption. The findings confirm that mental resilience is a foundational pillar that mediates technology adoption and eliminates workplace resistance. As a concrete recommendation, library leaders and professional organizations (such as IPI) must restructure training curricula by integrating modules on pure computing, technology-related stress management, and virtual counseling to ensure the sustainable resilience of the librarian profession.